PENGARUH PENINGKATAN KONSENTRASI PATI BIJI ALPUKAT (Persea americana Mill.) SEBAGAI PENGIKAT TERHADAP KARAKTERISTIK FISIK GRANUL DAN TABLET EKSTRAK AKAR ALANG-ALANG (Imperata cylindrica Linn.) - Dyah Hana Kartika; Mutmainah Mutmainah; Mufrod Mufrod (Faculty of Pharmacy, Universitas Gadjah Mada, 2012)
This research aims to determine the effect of avocado seed starch as a binder to the physical characteristics of the granule that is flow rate, angle of repose and moisture content as well as to the physical characteristics of tablets that is uniformity of weight, hardness, friability and disintegration time. Root of Imperata cylindrical (Linn.) extract was obtained by remaceration process usingethanol 70 % as a solvent. Tablets were made by wet granulation method with increase the avocado seed starch concentration as binder tablet (FI: 10 %, FII: 20 %, and FIII: 30 %) then the physical characteristics of granule and tablets were tested. Data were analyzed theoretically by comparing toliterature and statisticaly using one way ANOVA with a level of confidence up to 95 %, followed by Scheffe test. The results showed that the granule’s flow rate andangle of repose decrease byincreasing of avocado seed starch concentrations as a binder, while will increase the moist content of granules. Increasing of avocado seed starch concentration as a binder will increase the hardness and disintegration time of tablets as well, while friability of tablets are decrease and weight of tablets are more uniform.